FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DENGAN KESADARAN PERPAJAKAN SEBAGAI VARIABEL MODERATING - Yuliani, Siti Dewi; Setyaningsih, Nina Dwi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
The development of Business, Micro, Small, Medium Enterprises (UMKM) in Indonesia is currently experiencing a very drastic increase. The development of UMKM from year to year shows a significant number. This increase makes UMKM have enormous potential for the country's income. This study aims to describe whether perceptions of fairness, taxation security, changes in tax rates affect taxpayer compliance with tax awareness as a moderating variable for UMKM players after the application of PP No. 23 of 2018. This research employed quantitative methods. Moreover, respondents in this research were UMKM entrepreneurs registered at KPP Pratama Bojonegoro. The researcher used simple random sampling as the method of sampling where the distribution of questionnaires was done randomly without considering the level in a population. Furthermore, data collection was done by using a questionnaire technique. The results of this study explain that the variable Justice Perception (X1) influences Taxpayer Compliance proven by the significant value of 43.2%, Taxation Understanding (X2) controls Taxpayer Compliance as evidenced by the considerable amount of 74.5%, The Changes of Rates do not affect the Taxpayer Compliance as evidenced by significant value of 28.8%, and Tax Awareness (M) is not a variable that strengthens or weakens the relationship.